Isolation of extracellular vesicles: Determining the correct approach (Review) - SZATANEK, RAFAL; BARAN, JAREK; SIEDLAR, MACIEJ; BAJ-KRZYWORZEKA, MONIKA (International journal of molecular medicine, 2015)
The discovery of extracellular vesicles (EVs) has revised the interpretation of intercellular communication. It is now well established that EVs play a significant role in coagulation, inflammation, cancer and stem cell renewal and expansion. Their release presents an intriguing, transporting/trafficking network of biologically active molecules, which are able to reach and modulate the function/behavior of the target cells in a variety of ways. Moreover, the presence of EVs in various body fluids points to their potential for use as biomarkers and prognostic indicators in the surveillance/monitoring of a variety of diseases. Although vast knowledge on the subject of EVs has accumulated over the years, there are still fundamental issues associated with the correct approach for their isolation. This review comprises the knowledge on EV isolation techniques that are currently available. The aim of this review was to make both experienced researchers and newcomers to the field aware that different types of EVs require unique isolation approaches. The realization of this 'uniqueness' is the first step in the right direction for the complete assessment of EVs.